Breast Cancer Pathology Turnaround Time in Botswana - Martei, Yehoda M. (J Glob Oncol, 2017)
PURPOSE: Quality pathology is critical for timely diagnosis and management of breast cancer. Few studies have analyzed pathology turnaround time (TAT) in sub-Saharan Africa. The purpose of this study was to quantify TAT for breast cancer specimens processed by the National Health Laboratory and Diagnofirm Laboratory in Gaborone, Botswana, and additionally compare TAT before and after 2012 to evaluate the effect of pathology scale-up interventions by the Ministry of Health and Wellness. METHODS: Retrospective analyses of TAT were performed for breast specimens submitted to the two laboratories from 2011 to 2015. TAT was calculated as the time from specimen collection and receipt in the laboratory to the date of final report sign-out. Descriptive statistics and rank sum test were used to compare temporal trends in TAT before and after 2012. RESULTS: A total of 158 breast biopsy, 219 surgical, and 218 immunohistochemistry (IHC) specimens were analyzed. The median TAT in 2015 was 6 and 7 days for biopsy and IHC specimens, respectively, and 57.5 days for surgical specimens. There was a significant decrease in median TAT for biopsy specimens from 21.5 days in 2011 to 2012 compared with 8 days in 2013 to 2015 (P < .001). There was also a significant decrease in median TAT for IHC specimens during the same period (P < .001). However, there was no significant decline in median TAT for surgical specimens. CONCLUSION: The scale-up of pathology personnel and infrastructure by the Ministry of Health and Wellness significantly reduced median TAT for biopsy and IHC specimens. TAT for surgical specimens remains suboptimal. Efforts are currently under way to decrease TAT for surgical specimens to 7 days.